Flow balancing in extrusion dies for thermoplastic profiles Part II: Influence of the design strategy - Carneiro, O. S. (2003)
To achieve a specified geometry for an extruded profile with minimal level of stress gradient induced by pulling, flow balancing of the die is required. To fulfil this requisite, a set of operating conditions and polymer rheological properties is considered during the design step. However fluctuations of the operating conditions and/or slight variations of the polymer rheological properties are expected to occur during long-term production. Their effect on the performance of an extrusion die will depend, among other things, on the sensitivity of the flow distribution within the die. In this work, an extrusion die is optimised (balanced) using four different design methodologies and the final shapes of the die are compared in terms of their absolute quality (when used in the optimal conditions) and stability to the factors considered. For this purpose, a finite-volume based computational code is used to perform the required simulations of the non-isothermal three-dimensional flows, under conditions defined by a statistic Taguchi technique. The influence of some operating conditions on the flow distribution is assessed and the effect of the polymer melt rheology is also investigated. It was concluded that the use of different design methodologies lead to different results in terms of flow balancing and sensitivity to the factors considered and that the most balanced and stable extrusion die was that generated by the strategy based on the parallel zone thickness control.